PENGGUNAAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP PENINGKATAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI SISTEM PERNAPASAN MANUSIA DI MAN 1 SIGLI KABUPATEN PIDIE - Nawalul Faizin; Khairil Khairil; Mustafa Sabri (Biotik, 2017)
The aim of this study is to determine the differences of students’ cognitive learning outcome through project based learning method and conventional one. To collect the data, an experimental research is conducted by using pretest – posttest control group design. The samples were the second semester students of class XI of MAN 1 Sigli, Pidie regency which consisted of 66 students (33 students of class XI IPA-2 and 33 students of class XI IPA-3). Project based learning method was implemented in experimental class; meanwhile conventional method was implemented in control class. The data were analyzed by using independent sample t-test with SPSS 16.0 for Windows at significant level of 0.05. The result showed that there was a significant improvement of cognitive learning outcome of experimental class students (tcount7,156 > 2,000). It can be concluded that project based learning can increase students’ cognitive achievement.